Current magnetic resonance imaging characteristics of the most frequent granulomas of the brain - Castro-Magluff, Conrado (2023)
Infectious and non-infectious brain granulomas are a constant diagnostic challenge as, from the clinical point of view, present symptoms and signs, auxiliary tests, and images of very similar characteristics, delaying treatment and demanding an accurate histopathological diagnosis. Only recently, based on clinical experience, epidemiology, and new magnetic resonance techniques, the possibility of a non-invasive diagnosis is most likely. The infectious variants are more frequently found in regions of Latin America, Asia, and Africa, even though, due to migrations and globalization, they are also increasingly appearing in the rest of the world. The present work describes the entities that produce granulomas more frequently, and the diagnostic support currently provided by magnetic resonance imag.